Development of Community Based Tourism Destinations Through Collaborative Governance in Tanjungsari Village, Sadananya District, Ciamis Regency - Usep Indra Irawan; Kiki Endah (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2024)
This research is motivated by the lack of maximum development of natural tourism destinations in Tanjungsari Village, Sadananya District, Ciamis Regency. The purpose of this study is to find out the collaboration between the village government and the community in the development of tourist destinations. The research method used in this study is a descriptive research method with a qualitative approach, the data collection technique used by the author in this study is a literature study and a field study consisting of observation, interviews, and documentation. Meanwhile, data analysis techniques are carried out by data reduction, data processing, conclusion drawing and verification. Based on the results of the research, it is known that the collaboration between the village government and the community in the development of community-based tourist destinations in Tanjungsari Village, Sadananya District, Ciamis Regency has been running quite optimally.